SUBSURFACE UTILITY NETWORK CADASTRE PROPOSAL, BASED ON LADM (ISO / FDIS 19152) - Silva, Wedja de Oliveira; Carneiro, Andrea Flávia Tenório (Boletim de Ciências Geodésicas, 2020)
The increasing usage of the space above and underneath the land surface brings up the need of controlling its occupation. The localization of the infrastructure underground network is a major challenge, and for most of the countries, this information is not yet available or not easy to access. At this juncture, the cadastre of the network location is of fundamental importance for the water management supply systems. ISO 19152 from 2012 - Land Administration Domain Model (LADM) - addresses the standardization and integration of common features of cadastre systems in a simple way, and may be applied to several aspects of land administration. Within this context, this research aims to develop a model of subsurface water utility networks, based on the standard proposed by LADM. The implementation of the model suggested by ISO 19152 was tested using the COMPESA cadastre of the water utility network as a study case. The modernization and the technological advances adopted by the company facilitated the understanding of the geographical database underlying structure and its adaptation to the international standard. The modeling was produced using UML language, and DBDesigner for the physical implementation, executed in connection with PostgreSQL/PostGIS and QGIS, was applied.